2019
DOI: 10.3390/su11236852
|View full text |Cite
|
Sign up to set email alerts
|

Using the Fuzzy Delphi Method to Study the Construction Needs of an Elementary Campus and Achieve Sustainability

Abstract: One of the crucial concerns for achieving a campus’s sustainable development is that the school buildings should meet the needs of students and teachers. The design of school buildings should not only facilitate teaching activities but also provide a teaching environment that stimulates or encourages autonomous learning in students. School buildings are the site of classroom instruction and also serve as a teaching tool that helps in achieving educational objectives and providing compulsory education. They mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In the past 23 years, it has hosted many tea competitions at all levels and won more than 20 national and provincial tea competitions. e College of Horticulture and Landscape Architecture has been running a regular floral arrangement skills competition for students from the province since 2012, with a series of activities such as precompetition coaching, floral arrangement training, and master lectures at different levels [11]. On the one hand, the competitions enrich the students' lives after school, increase their motivation to study, enable them to learn and think about another skill to earn a living, and broaden the path of graduation competition for university students; on the other hand, the development of such subject skills competitions is a great support to the school's overall academic style construction work, which is of great importance.…”
Section: The Connotation Of Academic Style Building and Subject Skill...mentioning
confidence: 99%
“…In the past 23 years, it has hosted many tea competitions at all levels and won more than 20 national and provincial tea competitions. e College of Horticulture and Landscape Architecture has been running a regular floral arrangement skills competition for students from the province since 2012, with a series of activities such as precompetition coaching, floral arrangement training, and master lectures at different levels [11]. On the one hand, the competitions enrich the students' lives after school, increase their motivation to study, enable them to learn and think about another skill to earn a living, and broaden the path of graduation competition for university students; on the other hand, the development of such subject skills competitions is a great support to the school's overall academic style construction work, which is of great importance.…”
Section: The Connotation Of Academic Style Building and Subject Skill...mentioning
confidence: 99%
“…The data collected from this panel of experts is often complicated and unstructured. Therefore, another multicriterial decision-making method such as AHP is needed to integrate the subjective and objective perceptions of the experts and harmonize the criteria and the alternative elements into a hierarchical structure [56]. These two methods are commonly used together because they complement each other in a non-fuzzy environment [57].…”
Section: Developing a Localized Composite Resilience Index Based On D...mentioning
confidence: 99%
“…Sustainability 2021, 13, 8588 2 of 17 The EC has proposed achieving the general objective of reducing GHG emissions by 80% by 2050. In the "Roadmap for Moving to a Competitive Low-Carbon Economy in 2050", it is suggested that the most profitable way would be a reduction in the order of 20% every ten years.…”
Section: Introductionmentioning
confidence: 99%
“…The responsibility of universities in this regard must particularly be mentioned, as their ability to influence has two facets. On the one hand, the students will be the leaders of the future [10,11] and, on the other hand, university campuses can be considered as 'small cities', so their environmental impact must be ascertained and reduced [10,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%